DO CLUSTER FARMING PRACTICES IMPROVE PROFITABILITY AND PRODUCTIVITY INDICES OF SMALLHOLDER RICE FARMERS? EVIDENCE FROM BORNO STATE, NIGERIA - Abdulsalam Alkali Goni; Yusuf Usman Oladimeji; Jamila Rabe Mani; Abdulazeez Shero Isah (Socio-Economics/Agribusiness Department, 2023)
The study examined the comparative analysis of technical efficiency of cluster and non-cluster rice farming in Borno state, Nigeria. Primary data were collected through structured questionnaire administered to 232 farmers comprising of 93 clustering and 139 non-clustering rice farmers in Borno State, Nigeria. Data were subjected to analytical techniques that included descriptive statistics, gross margin, t-test and stochastic frontier production function (SFPF). Cluster rice farming enterprise per hectare was more profitable by producing a gross margin (GM) of 196,020.62/ha thus returning N1.72 on every N1.00 invested as compared to non-cluster farming which produced a GM of 99,619.32/ha and thus had a return of N0.96 on every N1.00 invested. The SFPF revealed an average technical efficiency (TE) of 0.76 for cluster farming was higher than 0.58 for non-cluster farmers. Hence, cluster rice farming was more technically efficient compared to non-cluster rice farming. The determining factors of TE in cluster farming include seed (-0.49), fertilizer (0.242), agro-chemicals (0.341) and labour (0.747) compared to non-cluster which included fertilizer (0.207), agro-chemicals (-0.291) and labour (0.668). Inefficiency variables were insignificant in cluster farming while household members active in farming (0.811), years of farming experience (-0.226), and amount of credit utilized (0.5e-4) were statistically significant in non-cluster farming. Insecurity, pest infestation and shortage of water were critical production constraints faced by cluster farmers compared to non-cluster farmers faced with constraints such as shortage of water, insecurity and flooding. Non-clustering farmers should adopt production cluster farming to boost their profit, increase their efficiency and take advantage of the enormous services attributed to working in groups.